2016
DOI: 10.7554/elife.20560
|View full text |Cite
|
Sign up to set email alerts
|

Sub-synaptic, multiplexed analysis of proteins reveals Fragile X related protein 2 is mislocalized in Fmr1 KO synapses

Abstract: The distribution of proteins within sub-synaptic compartments is an essential aspect of their neurological function. Current methodologies, such as electron microscopy (EM) and superresolution imaging techniques, can provide the precise localization of proteins, but are often limited to a small number of one-time observations with narrow spatial and molecular coverage. The diversity of synaptic proteins and synapse types demands synapse analysis on a scale that is prohibitive with current methods. Here, we dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…The synapse detection methodology described here is not the first to grapple with the challenges of detecting synapses in immunofluorescence images [ 6 ] [ 7 ] [ 8 ] [ 9 ] [ 10 ]. The special utility and novelty of this tool partially lies in (1) producing outputs in the form of probability maps, reflecting the limited certainty with which synapses can be detected by most experimental modalities [ 11 ], and (2) the superior utility for both interactive and algorithmic exploration which is conferred by the query-based architecture resulting from the unsupervised framework.…”
Section: Introductionmentioning
confidence: 99%
“…The synapse detection methodology described here is not the first to grapple with the challenges of detecting synapses in immunofluorescence images [ 6 ] [ 7 ] [ 8 ] [ 9 ] [ 10 ]. The special utility and novelty of this tool partially lies in (1) producing outputs in the form of probability maps, reflecting the limited certainty with which synapses can be detected by most experimental modalities [ 11 ], and (2) the superior utility for both interactive and algorithmic exploration which is conferred by the query-based architecture resulting from the unsupervised framework.…”
Section: Introductionmentioning
confidence: 99%
“…321 Multiplexed imaging applying a new computational method called SubSynMAP (SUB-SYNaptic, multiplexed analysis of proteins), which enables evaluation of several synaptic markers in multiple synapses in large brain areas at subdiffractional resolution, was also tested in Fmr1KO mice. 436 The method is based on a combination of deconvolution array technology, electron microscopy computation synapse classification, and synapse alignment using a variety of synaptic protein localization profiles. Using large data sets, this combination allows parallel investigation and comparison of several proteins in synaptic compartments to obtain information on their probability distribution.…”
Section: Sr-imaging In Models Of Neurodegenerative and Neurodevelopme...mentioning
confidence: 99%
“…FMRP deletion in Fmr1KO mice, however, leads to layer-specific deletion of FXR2P whereas localization of FXR1P remains unchanged. 436 Recent studies suggest that super-resolving microscopy may also become a valuable tool in advanced and probably also routine diagnostics of disease. In a proof-of-concept study, this was demonstrated by an increased detection rate of lowdensity cell surface antigens in myeloma cells.…”
Section: Sr-imaging In Models Of Neurodegenerative and Neurodevelopme...mentioning
confidence: 99%
See 1 more Smart Citation
“…a Nanoscale localization of multiple synaptic proteins along transynaptic axis, generated from 36,977 individual mouse cortical synapses (from Fig. 4 in [ 93 ]). b Variations with depth of volume density and size of seven molecular synapse types in mouse somatosensory cortex (from Fig.…”
Section: What Limits Fm-at Resolution?mentioning
confidence: 99%